Adaptive Development of Soil Bacterial Communities to Ecological Processes Caused by Mining Activities in the Loess Plateau, China - Luo, Zhanbin (Microorganisms, 2020)
Microorganisms are the driving force behind the circulation and transformation of the soil substance. The development of soil bacterial communities is critical for ecosystem restoration and evolution. In the Loess Plateau, coal mining activities have aggravated the deterioration of the fragile local ecological environment. The adaptive development of soil bacterial communities in response to different ecological processes caused by coal mining activities was explored through high-throughput sequencing technology and an ecological network analysis of the mining subsidence area of the Daliuta Coal Mine and vegetation rehabilitation area of the Heidaigou Coal Mine in the Loess Plateau. The results showed that while mining subsidence was inhibited, vegetation rehabilitation promoted the soil physicochemical properties. Soil organic matter, available phosphorus and available potassium in the subsidence area decreased significantly (P < 0.05), while soil organic matter, soil water, pH and EC in the vegetation rehabilitation area increased significantly (P < 0.05). The diversity index in the subsidence area decreased by about 20%, while that in the vegetation rehabilitation area increased by 63%. Mining subsidence and vegetation rehabilitation had a distinct influence on the molecular ecological networks of the soil bacteria, which tended to be more complex after the mining subsidence, and the number of connections in the network increased otherwise significantly enhanced interactive relationships. After the vegetation rehabilitation, the number of modules in the ecological network increased, but the contents of modules tended to be simpler. Soil bacterial communities adapted to the changes by changing the relationships between bacteria in response to different ecological processes. This study provides new insights into the monitoring and abatement of the damaged ecological environment in mines.